Enhanced ion transport behaviors in composite polymer electrolyte: the case of a looser chain folding structure. Issue 6 (19th January 2022) - Pei, Dexuan; Ma, Rui; Yang, Gang; Li, Yuhang; Huang, Can; Liu, Ziying; Huang, Shuo; Cao, Guozhong; Jin, Hongyun
Abstract : CPEs with smaller size of Al2 O3 nano-particles leads to shorter spin-lattice relaxation time ( T 1 ) and longer transverse relaxation time ( T 2 ), implying a looser chain folding structure in CPEs, which provides more transport channels and conducting pathways for the Li-ions transportation. Abstract : All-solid-state batteries based on composite polymer electrolytes (CPEs) have attracted significant attention due to their high energy density, security and flexibility. Usually, the enhanced electrochemical performance of CPEs is attributed to the reduction in crystallinity in the polymer matrix by introducing inorganic fillers. However, studies on the effects of the change in the chain folding structure in polymers on the ion transport behaviors after the addition of fillers are limited. In this work, we fabricated CPEs with different-size inorganic Al2 O3 nanofillers. The results showed that CPEs with smaller-size Al2 O3 nanoparticles exhibited shorter T 1 and longer T 2 relaxation times, implying the looser chain folding structure in these CPEs. Particularly, the CPEs with 30 nm-sized Al2 O3 particles exhibited good conductivity of 4.87 × 10 −5 S cm −1 and high Li + transference number of 0.65. We conclude that the looser chain folding structure in the polymer matrix, which provides more channels for Li + transport, plays a major role in improving the electrochemical properties of the electrolyte with an excellent capacity retention of 81.3% after 500 cycles at 1.0C in LFP/CPE/Li batteries. This provides novel insight to clarify the mechanism of the chain folding structure and how it influences the lithium ion transport, thus improving the electrochemical performances of CPEs.